States that did not pass the preliminary examinations of the OTP - Motillewa Quadri, Kafayat; Abia Kadouf, Hunud (International Scientific Academy of Engineering and Technology, 2015)
Abstract—The referred situation of a State passing all the required criteria for a preliminary examination happens when the Office of the Prosecutor (OTP) of the ICC comes to a safe assumption and conclusion that there is a reasonable belief that crimes under the jurisdiction of the ICC have been committed and that the situation is likely be admissible before the Court. Whilst, the process of a preliminary examination of a particular situation may take a few months; at other times it can take several years. Although, many may perceive preliminary examinations to be a political stall, it would seem that the OTP does actually have problems gaining the cooperation of some of the State governments that have their situations being examined by the ICC. This paper would look into the framework of preliminary examinations as carried out by the OTP according to the provisions of the Rome Statute; the expectations required from the States that are being examined and then be juxtaposed with the decision of the OTP with regards to the situations in Republic of Korea (South Korea), Registered Vessels Of Comoros, Greece And Cambodia; and Palestine.